Merchandising en CAFENET.JIREH.NET - Moreno Triana, Zuly Mariana (2021)
This research is based on the analysis of merchandising techniques in "CAFENET.JIREH.NET" due to the fact that problems are observed due to an inadequate distribution of the products on the hangers, it has little space that it is impossible for each product to be distributed correctly and efficiently to achieve customer satisfaction. It also has as a weakness the lack of prices in the products, which generates confusion and discontent; but it is important to note that it has seven trained and motivated workers to create a calm work environment with excellent communication with users. It has efficient management of stock management and therefore it manages to be efficient, which is one of its strengths. It is important to mention that "CAFENET.JIREH.NET" correctly uses digital merchandising, motivating customers to purchase its products through the social networks that are used daily, although it is true that this marketing strategy was used full time at times pandemic, for biosecurity reasons, it was implemented satisfying customer needs and increasing the level of sales within the business. Generating promotions, raffles and offers of the products and in this way encouraging the purchase of the items that you are offering.